Improvement on Electrochemical Nitrate Removal by Combining with the Three-Dimensional (3-D) Perforated Iron Cathode and the Iron Net Introduction. Issue 14 (1st January 2016) - Kuang, Peijing; Feng, Chuanping; Chen, Nan; Hu, Weiwu; Wang, Gen; Peng, Tong; Lv, Long
Abstract : Nitrate contamination in groundwater became an ever-increasing serious environmental problem and some conventional electrochemical methods had the higher energy consumption and the lower efficiency. This study constructed an intensified system by introducing bipolar iron net between the three-dimensional (3-D) perforated iron cathode and Ti/IrO2 -Pt anode to improve nitrate removal efficiency. The 3-D perforated iron cathode constructed by two pieces of iron net series connection had larger specific surface area and lower impedance for promoting nitrate reduction. Tafel analysis and cyclic voltammetric (CV) measurements showed that nitrate electroredcution and chemical nitrate reduction by Fe 0 with iron corrosion could be achieved by introducing the iron net near the anode (NA) or in the middle of electrodes (IME), sequentially increasing nitrate reduction efficiency. Comparing with nitrate reduction efficiency and energy consumption reported in the previous study, higher nitrate reduction efficiency of 90.1% and lower energy consumption of 34.76 kWh/n-nitrate-N were obtained by introducing three pieces of iron net between electrodes in the presence of 0.75 g/L NaCl without ammonium or nitrite accumulation. It was observed that iron corrosion products covered on the surface of iron net introduced NA or IME. The developed electrochemical system was proved to be suitable for accelerating nitrate removal.